INFO: An efficient optimization algorithm based on weighted mean of vectors - Ahmadianfar, Iman; Heidari, Ali Asghar; Noshadian, Saeed; Chen, Huiling; Gandomi, Amir H (Expert systems with applications, 2022)
•A novel weighted mean of vectors (INFO) is proposed for global optimization.•The performance of INFO is verified by comparison against other competitive algorithms.•INFO has faster convergence speed and accuracy compared with others.•INFO was validated on 48 functions and four remarkable engineering test cases.•Excellent results have been obtained in engineering experiments. This study presents the analysis and principle of an innovative optimizer named weIghted meaN oF vectOrs (INFO) to optimize different problems. INFO is a modified weight mean method, whereby the weighted mean idea is employed for a solid structure and updating the vectors’ position using three core procedures: updating rule, vector combining, and a local search. The updating rule stage is based on a mean-based law and convergence acceleration to generate new vectors. The vector combining stage creates a combination of obtained vectors with the updating rule to achieve a promising solution. The updating rule and vector combining steps were improved in INFO to increase the exploration and exploitation capacities. Moreover, the local search stage helps this algorithm escape low-accuracy solutions and improve exploitation and convergence. The performance of INFO was evaluated in 48 mathematical test functions, and five constrained engineering test cases including optimal design of 10-reservoir system and 4-reservoir system. According to the literature, the results demonstrate that INFO outperforms other basic and advanced methods in terms of exploration and exploitation. In the case of engineering problems, the results indicate that the INFO can converge to 0.99% of the global optimum solution. Hence, the INFO algorithm is a promising tool for optimal designs in optimization problems, which stems from the considerable efficiency of this algorithm for optimizing constrained cases. The source codes of INFO algorithm are publicly available at https://imanahmadianfar.com. and https://aliasgharheidari.com/INFO.html.